The RN to BSN Transition - Allison Brandt Anbari (SAGE Publishing, 2015)
Approximately 60% of registered nurses (RNs) still enter practice with an associate's degree or diploma in nursing (ADN). Due to recommendations to change entry level to practice to the bachelor's degree in nursing (BSN), there are now more than 700 RN to BSN programs in the United States. The purpose of this qualitative systematic review was to understand more about what occurs when an RN returns to school for a BSN and to develop a model of the transition. The qualitative findings of 19 research reports were included, which translates to approximately 445 RNs' perspectives on the RN to BSN transition. A visual representation of the RN to BSN transition was also generated. A seamless transition of the RN to a BSN does not exist at this time. The results are useful to nurses, academicians, and health care organizations as they move to meet current recommendations.